When They Try To Erase Us - Dr. Terriyln Rivers-Cannon (International Journal of School Social Work, 2025)
The history of social work in the United States has been marked by both progress and paradox. While the profession prides itself on values of equity, inclusion, and social justice, its very foundation has often mirrored societal hierarchies that exclude, minimize, or erase the contributions of practitioners of color. This article explores how erasure functions within the field of school social work from the historical invisibility of Black, Indigenous, and other leaders of color to the contemporary marginalization of their voices in policy, research, and leadership narratives. Grounded in critical race theory, intersectionality, and social work ethics, this practitioner-centered analysis examines the psychological and professional toll of erasure while illuminating the resilience, innovation, and transformative leadership of those who refuse to be silenced. The article concludes with a call-to-action urging institutions, associations, and practitioners to reckon with history, restore recognition, and reimagine leadership that truly embodies social justice.
Keywords: school social work; leadership equity; racial justice; critical race theory; intersectionality; diversity and inclusion; cultural taxation; practitioner voice; educational equity